Efektivitas Pembelajaran Daring Pada Materi Hukum Hooke Menggunakan LMS berbasis Edmodo - Muspa, Rizky Merian; Sulisworo, Dwi (Jurnal Penelitian Pembelajaran Fisika, 2022)
This study aims to determine the effectiveness of online learning on hooke law material using edmodo-based lms, the method used is to analyze the questionnaire given to respondents via google form, the subject of this study is class XI SMA N 1 Lahat, this research divides 3 topics. In the survey, the use of Edmodo in terms of the aspect of ease, the use of Edmodo in terms of the aspect of language structure and use of Edmodo in terms of the aspect of presentation. Based on the survey results from the aspect of convenience in Figure 4, the data obtained respectively 3,867 - 3,8 - 3,73. Which means that it has an average in the good category. Next, the survey results from the aspect of language structure in Figure 5, respectively, obtained data from 3.8 to 3.93 - 3.73, which means that it has an average in the good category. And the survey results from the presentation aspect in Figure 6 respectively obtained data 3,867 - 3,867 - 3,93 which means that it has an average in the good category. Of the three types of surveys that have been conducted, it can be categorized that the results of this study are good, so it can be said that this research is able to increase the effectiveness of learning and is suitable for use in the learning process.Keywords: LMS, Effectiveness of Learning Physics, Edmodo.